The Australian Accounting Standards Review Board: The Establishment of its Participative Review Process. - Wrege, W. T. (The Accounting Review, 1993)
Reviews the book "The Australian Accounting Standards Review Board: The Establishment of Its Participative Review Process," by Asheq Razaur Rahman.